Health outcomes up to 5 years in children born as a second child after a previous caesarean section in a first pregnancy: a Swedish population-based register study between 1999 and 2015 - Anna Dencker; Anders Elfvin; Valerie Smith; Lars Ladfors; Huiqi Li; Ingela Lundgren; Ida Lyckestam Thelin; Christina Nilsson (BMJ Paediatrics Open)
Objective To explore health outcomes up to 5 years of age, according to mode of birth, in a large cohort of Swedish children who were born as a second child to women who had a caesarean section (CS) in their first pregnancy.Design Retrospective population-based register study.Population All children (n=94 498) who were born as a second child (or children in cases of twins or higher-order multiple births) during 1999–2015 in Sweden in women who had a CS first birth. The children were followed up to 5 years of age. For inclusion, both births must have occurred in Sweden.Methods A nationwide cohort study using follow-up data up to 5 years of age. Maternal factors, including age, smoking, diabetes, obesity (body mass index ≥30), mental illness, pre-eclampsia, education, income, country of birth and the neonatal factors of being a singleton and prematurity (up to week 36+6) were adjusted for in regression models.Main outcome measures Developmental problems, asthma, allergy, hospital care and death within 5 years of age.Results A total of 94 498 children were included in the study. Risk for developmental problems, asthma and allergy was increased after repeat CS but not after vaginal birth. The need for hospital care was increased in all other birth modes compared with spontaneous vaginal birth. The risk of death within 5 years increased after instrumental vaginal birth and emergency repeat CS.Conclusions All repeat CS compared with spontaneous vaginal birth was related to increased risks for developmental problems, asthma, allergy and hospital stay, and emergency repeat CS was associated with an increased risk of death within 5 years. The results of the present study support vaginal birth as the optimal mode of birth after previous CS for longer-term child health outcomes.